Asparagus breeding: Future research needs for sustainable production - Drost, Daniel (Frontiers in Plant Science, 2023)
Productivity in asparagus (Asparagus officinalis L.) is determined in part by (1) the selection of superior, adaptive genetics, (2) matching the selected genetics to the production environment, and (3) managing the crop production system in ways to maximize harvest potential that are sustainable, profitable, and efficient. Over the last 100 years, a considerable effort by asparagus researchers has gone into breeding superior genetic lines, testing those in numerous locations, and studying how asparagus responds to a multitude of inputs (fertilizers, irrigation, fungicides, herbicides, insecticides). Farmers worldwide have benefited from all of these improvements. However, as we look to the future, we need to change our research approaches to deal with widely accepted limitations to asparagus growth that if left unanswered will further erode the long-term sustainability and profitability of the crop. In addition, there is a growing need for increased mechanization to offset labor needs. To effectively harvest asparagus, new plant types with more predictable spear emergence patterns need to be bred. This paper will briefly review the historic content of asparagus research and open a discussion on how to refocus international research efforts to breed superior plant materials to meet the challenges of the future.